Considerações sobre o bruxismo infantil - Gomes, Nathália Silva [UNESP] (2011)
Bruxism has been a constant subject of studies, both in dentistry and in other areas of Health. It is a complex topic, covering aspects multifactorial and its treatment consists in the completeness of various specialties. The favorable prognosis depends on accurate diagnosis by detecting the main factor of its appearance. It affects children, adolescents and adults, both male and female, and its etiology has been questioned by many authors. The lines of research vary from author to author, but there is a consensus among them, in almost of the cases, bruxism has been frequently linked to emotional stress of the patient, and then he grinds his teeth to release repressed emotions, frustrations and preoccupations. This study aimed to do a synthesis of literature review on childhood bruxism and analyze the records of children aged 6-9 years, assisted in the last 2 years in the pediatric dentistry clinic of the Undergraduate College of Dentistry of Araçatuba/SP-UNESP, for the survey on the number of children with bruxism in order to schedule them for monitoring, guidance and treatment if necessary. From a total of 500 records analyzed, it was found only 67 children who have or have had, at some point in their lives, the habit of grinding teeth. In this study, it was observed that the act of grinding teeth sporadically and without clinically visible dental abrasion were not diagnosed with true bruxism, but such as occasional demonstrations of momentary emotional problems. Also, it was observed a slightly higher occurrence of these phenomena in males. The results of this study are in agreement with those found in the literature that describing small number of children with bruxism, in the same age group like ours, because we found only 15 children with bruxism that showed significant tooth abrasion, from a total of 500 records of children examined